2007
DOI: 10.1080/00365520600988212
|View full text |Cite
|
Sign up to set email alerts
|

Liver involvement in acute vaso-occlusive crisis of sickle cell disease: Prevalence and predisposing factors

Abstract: In SCD, there is a 39% prevalence of acute veno-occlusive involvement of the liver, a figure that is much higher than previously reported. The type of injury is mostly mixed hepatocellular-cholestatic or purely cholestatic and its course is usually benign. Liver involvement occurs more often in patients with normal spleen function and is not associated with the overall severity of the acute episode, both observations being unreported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
2
20
1
1
Order By: Relevance
“…17 In the cohort of patients in this manuscript, both ALT and ALP correlated with increasing TE during VOC. However, TE was also noted to increase in some who did not have substantial increases in ALT or ALP suggesting that increase in liver stiffness is not always reflected in biochemical changes.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…17 In the cohort of patients in this manuscript, both ALT and ALP correlated with increasing TE during VOC. However, TE was also noted to increase in some who did not have substantial increases in ALT or ALP suggesting that increase in liver stiffness is not always reflected in biochemical changes.…”
Section: Discussionmentioning
confidence: 76%
“…9,17,47,48 It has been suggested that this is due to widespread sickling with resultant obstruction in the sinusoids leading to hepatocyte anoxia and ischemia, and ultimately necrosis and death. Available definitions of hepatic involvement in acute VOC are imprecise given the overlap between sickle cell and hepatic serum biochemical parameters and the poor correlation of the serum biomarkers with acute VOC, which was corroborated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in accordance with the results of other studies that reported a high frequency of liver complications in adult SCD patients and their improvement under HU therapy. 21,23,24 Avascular necrosis of bone (ANB) is another frequent and severe complication of SCD. 25,26 In the LaSHS study, at baseline, 12% of patients had a history of symptomatic ANB; a result comparable with that of Milner et al, 25 who found a prevalence of 10% of ANB in 2590 patients with SCD.…”
Section: The Effect Of Hu On Chronic Complications Of Scdmentioning
confidence: 99%